2011
DOI: 10.1016/j.bbmt.2011.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive Immunotherapy with Cytokine-Induced Killer Cells for Patients with Relapsed Hematologic Malignancies after Allogeneic Hematopoietic Cell Transplantation

Abstract: Donor leukocyte infusions induce remissions in some patients (pts) with hematologic malignancies who relapse after allogeneic hematopoietic cell transplantation (HCT). However, graft vs host disease (GVHD) remains the major complication of this strategy. Cytokine induced killer (CIK) cells are a unique population of cytotoxic T lymphocytes that express the CD3+CD56+ phenotype and show marked upregulation of the NK cell receptor, NKG2D (CD314). CIK cells are non-MHC restricted, and NKG2D dependent in target rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
99
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 23 publications
6
99
0
1
Order By: Relevance
“…Thus far, CIK cell infusions had only been tested after matched-donor allogeneic transplantation. 4,5,10 Our data demonstrate a similar safety and feasibility of CIK cell therapy from haploidentical donors.…”
Section: Total Number Of Cellssupporting
confidence: 65%
See 1 more Smart Citation
“…Thus far, CIK cell infusions had only been tested after matched-donor allogeneic transplantation. 4,5,10 Our data demonstrate a similar safety and feasibility of CIK cell therapy from haploidentical donors.…”
Section: Total Number Of Cellssupporting
confidence: 65%
“…Also other groups have reported limited efficacy of CIK cell infusions. 4,10 In our patients, CIK cell therapy may not have reached its full potential, as it was initiated during advanced disease. 1 In conclusion, these findings demonstrate the safety and feasibility of haploidentical CIK cell infusions, albeit in a small number of heterogeneous, pediatric patients, who in part had also received concomitant antitumor therapy.…”
Section: Total Number Of Cellsmentioning
confidence: 95%
“…Lymphocytes were separated and cultured as reported by Pan et al (12), and Laport et al (13) with certain modifications. Equivalent volumes of peripheral blood and 0.9% physiological saline were mixed followed with ficoll gradient separation (LymphoPrep; PAA Laboratories; GE Healthcare, Chicago, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…These trials have reported efficacy with well-tolerated toxicities in the treatment of patients with metastatic diseases, lymphoma and acute leukemia. For example, a recent Phase I dose-escalation trial by Negrin's group with allogeneic CIK cell infusions in patients with relapsed hematologic malignancies reached the planned maximum cell dose of 1 Â 10 8 CD3 + cells/kg as the maximum tolerated dose with low incidence of graft-versus-host disease (GVHD) paralleled to that reported in preclinical models [2] and provides further rationale of the clinical use of CIK cells.…”
mentioning
confidence: 95%